State of Lung Cancer in Egypt: Moving Towards Improved Guidelines for Prevention, Screening, Treatment, and Clinical Care Programs - Nagla Abdel Karim, MD; Ahmed Magdy Rabea, MD; Philip C. Mack, PhD; Janakiraman Subramanian, MD; Ehab Khalil, MD; Mai Sherif, MD; Radwa Marawan, MD; Tagrid Gaafar, MD; Lobna Shash, MD; Kei Suzuki, MD; Manmeet Ahluwalia, MD; Hisham Wahba, MD; et al. (JTO Clinical and Research Reports)
Lung cancer remains a leading cause of cancer-related mortality globally and presents significant challenges in Egypt. In 2023, the first annual meeting of the Thoracic Oncology Multidisciplinary Faculty, organized by the Egyptian Cancer Research Network and the Egyptian Society of Respiratory Neoplasms, was held in Cairo, Egypt. The meeting aimed to address gaps in lung cancer management across Egypt and the broader Middle East and North Africa region. The discussions focused on the challenges posed by NSCLC and SCLC and emphasized the need for enhanced prevention, early detection, and treatment strategies. Key areas of concern include limited access to advanced diagnostics, such as comprehensive genomic profiling, and the underutilization of targeted therapies and immunotherapies, mainly owing to financial barriers. The meeting highlighted the importance of strengthening lung cancer screening programs, improving smoking cessation efforts, and addressing environmental risk factors like air pollution. Furthermore, the event underscored the need for greater research and collaboration, particularly in areas like precision oncology. The conference concluded with strategic recommendations to improve lung cancer prevention, screening, and treatment, aligning Egypt’s lung cancer care with global advancements and ensuring equitable access to cutting-edge therapies.